Training and Development on the Performance of Administrative Staff in Ministry of Infrastructure and Communication- Zanzibar. - Ali Mohammed, Saada (Kabale University, 2020)
The study was assessing the Training and Development on the Performance of Administrative Staff in the Ministry of Infrastructure and Communication – Zanzibar and was guided by three objectives which were: to examine the existing training and development process used in the MOIC, To identify the impact of training and development activities on the performance of the administrative staff, to investigate the training and development activities on the organizational performance. A total sample of seventy (70) respondents was considered for the study. These included administrative staff of the MOIC and a Director of Administration and Human Resources. The study employed descriptive research design that helped in gathering information about the study. Both qualitative and quantitative data was collected and this enabled the researcher to draw valid and dependable conclusion and recommendation. The researcher also used both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included questionnaires, observation, and interview. Data collected was edited, coded, entered into computer and analyzed with excel, a Microsoft statistical package, the results were presented in tables. Basing on results from the study, from objective one above, it was found out that most administrative staff are aware that the training and development activities exist and are implemented in the MOIC. From the research, objective two it was found out as indicated by the respondents from MOIC that the training and development activities in MOIC were unplanned and unsystematic, This was because there was no specific training and development unit or department and also they do not have sufficient funds to meet the costs of training due to the low budgets provisions for the office expenditures that are always below the requests. The study discovered impacts of training development as it helped improve performance of work and the details were presented, analyzed and discussion. The study concluded that the training and development activities equipped administrative staff with new skills and technical knowledge of doing work as compared to the untrained administrative staff; the trained staffs are able to perform their job better.